Counseling And Social Psychological And Educational Guidance In Jordanian Educational Institutions - AL-Momani, Mohammad Omar; Rababa, Elham Mahmoud (Universitas Pendidikan Indonesia, 2023)
Social psychological helps us understand social interactions, conflict, communication, and group dynamics. Research in this field is often carried out through scientific methods such as experiments, surveys, observations, and statistical data analysis to reveal patterns of behavior and social influence in various contexts of daily life. The study aimed to identify reality Social Psychological and educational counseling and guidance in Jordanian educational institutions. To achieve the purpose of the study, the theoretical analytical qualitative approach was used, through an attempt to evaluate and examine the reality of the counseling process in Jordan. Based on results found that in the second semester of the academic year (2022/2023); Where the study concluded that the reality of counseling and social psychological and educational guidance in Jordanian educational institutions is applied and activated in a somewhat positive way, but the weakness of capabilities and resources prevents the realization of all the goals set correctly.